MAKNA SEMIOTIKA KOMUNIKASI DALAM TALKSHOW SARAH SECHAN DI NET. TV - Rachmadani, Nadia Puspita; Hambali (Universitas Muhammadiyah Kotabumi, 2021)
An Analysis a charming and unique television show, Sarah Sechan's talk show on the Net. TV always tries to present shows that are not only interesting, but also informative and entertaining so that they are received enthusiastically by viewers. In each episode of Sarah Sechan's talk show, there are various signs or signals in the context of communication, including from the stage, stage background, program theme song, and the words of Sarah Sechan (host/communicator) and guest stars (communicant), which of course have meaning that can be interpreted differently by viewers. This research adopts an interpretive and qualitative research method, where the specialist depicts the aftereffects of perceptions of communication semiotic analysis based on the ten types of signs in Charles Sanders Pierce's theory. Semuotics, as a science or method of analysis, is used to study signs. Communication semiotics focuses on signs or signals in a communication context that involves communication elements. From the examination results, it was presumed that the signs in Sarah Sechan's television show program capability as fascinating data and are not yet known to the overall population. The aim of this research is to find out whether there are signs or signal in the communication context that connect several aspects of communication in Sarah Sechan's talkshow program. The information presented in this program is not only unique and interesting, but also provides positive meaning to each viewer. Therefore it is worth watching as a source of meaningful entertainment.